Duration of antibiotic treatment for acute graft pyelonephritis: What's the standard of care?. Issue 1 (10th December 2022) - Kumar, Rebecca; Pereira, Marcus; Taimur, Sarah; True, Karin; Detwiler, Randall; van Duin, David
Abstract: Background: Limited evidence is available to inform the duration of antibiotic treatment in kidney transplant recipients with bacterial acute graft pyelonephritis. Guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation suggest a 14–21 day duration. Methods: A four‐question survey was constructed to determine the current standard of practice for the duration of treatment for acute graft pyelonephritis. The survey was distributed among members of the Infectious Diseases and the Kidney Pancreas Communities of Practice of the American Society of Transplantation. Results: Among 144 survey respondents, 87 (60%) were infectious disease physicians, and 36 (25%) were transplant nephrologists. Although most (55%) respondents preferred a 14‐day duration, a spread between 7 and 28 days was observed. Goals of treatment and drivers for longer duration differed between infectious disease physicians and transplant nephrologists. Conclusions: Although most respondents prefer a 14‐day duration of treatment for acute graft pyelonephritis, a wide range of responses was seen between 7 and 28 days. More evidence is needed to inform optimal treatment duration in this common infectious complication after transplantation. Abstract :